The unbalanced p53/SIRT1 axis may impact lymphocyte homeostasis in COVID-19 patients. (April 2021) - Bordoni, Veronica; Tartaglia, Eleonora; Sacchi, Alessandra; Fimia, Gian Maria; Cimini, Eleonora; Casetti, Rita; Notari, Stefania; Grassi, Germana; Marchioni, Luisa; Bibas, Michele; Capobianchi, Maria R.; Locatelli, Franco; et al.
Highlights: Significant reduction of SIRT1 in COVID-19 patients may play a role in the maintenance of p53 in the active form. Significant increase of p21 in COVID-19 patients may participate to cell cycle arrest. Inflammatory cytokines positively correlated with p53 and negatively with SIRT-1 and with BLNK expression. The inflammation, the dysregulated p53/SIRT-1 axis and IL7R/BLNK expression may impact cell survival, B cell signaling in COVID-19 patients. Abstract: Background/objectives: A dysregulated inflammatory profile plays an important role in coronavirus disease-2019 (COVID-19) pathogenesis. Moreover, the depletion of lymphocytes is typically associated with an unfavourable disease course. We studied the role and impact of p53 and deacetylase Sirtuin 1 (SIRT1) on lymph-monocyte homeostasis and their possible effect on T and B cell signalling. Methods: Gene expression analysis and flow cytometry were performed on peripheral blood mononuclear cells (PBMC) of 35 COVID-19 patients and 10 healthy donors (HD). Inflammatory cytokines, the frequency of Annexin+ cells among CD3+ T cells and CD19+ B cell subsets were quantified. Results: PBMC from COVID-19 patients had a higher p53 expression, and higher concentrations of plasma proinflammatory cytokines (IL1β, TNF-α, IL8, and IL6) than HD. Deacetylase Sirtuin 1 (SIRT1) expression was significantly decreased in COVID-19 patients and was negatively correlated with p53 (p = 0.003 and r = −0.48). A lower expression of IL-7R and B Cell linker (BLNK), key genes for lymphocyte homeostasis and function, was observed in COVID-19 than in HD. The reduction of IgK and IgL chains was seen in lymphopenic COVID-19 patients. A significant increase in both apoptotic B and T cells were observed. Inflammatory cytokines correlated positively with p53 (IL-1β: r = 0.5 and p = 0.05; IL-8: r = 0.5 and p = 0.05) and negatively with SIRT1 (IL1-β: r = −0.5 and p = 0.04; TNF-α: r = −0.4 and p = 0.04). Conclusions: Collectively, our data indicate that the inflammatory environment, the dysregulated p53/SIRT1 axis and low expression of IL7R and BLNK may impact cell survival, B cell signalling and antibody production in COVID-19 patients. Further studies are required to define the functional impact of low BLNK/IL7R expression during severe acute respiratory syndrome coronavirus-2 infection.